Factors contributing to the higher prevalence of suicide in Jhenaidah, Bangladesh: a qualitative exploration - Abdul Awal; Kamal Uddin Ahmed Chowdhury; Md Omar Faruk (BMJ Open, 2025)
Objectives Incidents of suicide remain a major public health concern worldwide, including in Bangladesh. Scholarly research in Bangladesh has primarily focused on factors contributing to the high prevalence of suicide and suicide attempts among students. However, there is limited research on the community-level factors contributing to suicide, particularly in Jhenaidah, a southeastern region in Bangladesh with a higher prevalence of suicide thoughts and behaviours. Therefore, this study aims to explore the factors responsible for the disproportionate rates of suicides and attempts in Jhenaidah.Design We used an exploratory qualitative study design.Participants A total of 48 participants (Male 29 and Female 19) were purposively recruited from six subdivisions of Jhenaidah. Participants who attempted suicide, their family members, community representatives and healthcare providers comprised the sample.Methods We conducted a semistructured in-depth interview with a purposively selected participant. Interviews were transcribed verbatim. Thematic analysis with the inductive method was used.Results Qualitative data analysis led to the emergence of six major contributing factors, each yielding at least one category and subcategory. These factors are broadly associated with interpersonal relationships, physiological and psychological complaints, a range of socioeconomic issues, educational and moral issues, and knowledge and accessibility of methods for suicide.Conclusions Results highlight the intricacies of various factors for the disproportionate rates of suicidal thoughts and behaviours in Jhenaidah and reinforce the importance of implementing a biopsychosocial perspective on suicide prevention. The results also contribute to the global understanding of suicide through the exploration of indigenous factors.